PENERAPAN MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PAI KELAS IX B SMP NEGERI 5 BATANG HARI TAHUN PELAJARAN 2022/2023 - Azizah (Najah Bestari, 2023)
The background of this research is the low learning outcomes of students in class IX at SMP Negeri 5 Batang Hari, which is caused by a lack of student learning activity. This is evidenced by students who are afraid to express opinions, often ask permission to study, learning is only dominated by smart students, etc., which results in low student learning outcomes. The purpose of this study is first, to find out the achievement of the application of the Problem Based Learning Learning Model in the material Achieving Success with Optimism of Endeavor and Tawakkal for class IX students of SMP Negeri 5 Batang Hari, second, to find out the learning outcomes of the material Achieving Success with Optimism of Endeavor and Tawakkal for students class IX SMP Negeri 5 Batang Hari after applying the Problem Based Learning model. The results of the study are first, the implementation of learning using the Problem Based Learning Model if it is carried out with good planning and mastery of concepts will work well, as expected. second, students become active in learning and begin to be trained with higher-order thinking patterns. Third, the Problem Based Learning Learning Model is proven to improve student learning outcomes. In the first cycle the achievement of student learning outcomes in the class average was 70.5, in the second cycle the class average was 73.5 and in the third cycle the class average was 81.7. While those who achieved learning mastery in cycle one were 64.7 percent, in cycle two 82.3 percent and in cycle three 94.1 percent. This shows that student learning outcomes using the Problem Based Learning Learning model have increased significantly, and research related to the use of Problem Based Learning Learning Models is considered successful.